Rapid Authentication of Coffee Blends and Quantification of 16‑O‑Methylcafestol in Roasted Coffee Beans by Nuclear Magnetic Resonance - Schievano, Elisabetta; Finotello, Claudia; De Angelis, Elisabetta; Mammi, Stefano; Navarini, Luciano (Journal of agricultural and food chemistry, 2014)
Roasted coffee is subject to commercial frauds, because the high-quality Coffea arabica species, described as “100% Arabica” or “Highland coffee”, is often mixed with the less expensive Coffea canephora var. Robusta. The quantification of 16-O-methylcafestol (16-OMC) is useful to monitor the authenticity of the products as well as the Robusta content in blends. The German standard method DIN 10779 is used in the determination of 16-OMC in roasted coffee beans to detect C. canephora in blends, but it is laborious and time-consuming. Here, we introduce a new method that provides a quantitative determination of esterified 16-OMC directly in coffee extracts by means of high-resolution proton nuclear magnetic resonance spectroscopy. Limit of detection and limit of quantitation were 5 and 20 mg/kg, respectively, which are adequate to detect the presence of Robusta at percentages lower than 0.9%. The proposed method is much faster, more sensitive, and much more reproducible than the DIN standard method.